The global village : transformations in world life and media in the 21st century - McLuhan, Marshall, 1911-1980; Powers, Bruce R. (New York : Oxford University Press, 1989)
The premise for this book is the distinction between what the authors call'visual space', which is the left-brain, linear, quantitative reasoning tradition of the West, beginning with Plato and Aristotle, as against'acoustic space', which is equated to the holistic approach of the East.
I. Explorations in visual and acoustic space. The resonating interval ; The wheel and the axle ; Visual and acoustic space ; East meets west in the hemispheres ; Plato and angelism ; Hidden effects -- II. The global effects of video-related technologies. Global robotism : the satisfactions ; Global robotism : the dissatisfactions ; Angels to robots : from Euclidean space to Einsteinian space -- III. The United States and Canada : the border as a resonating interval. Epilogue : Canada as counter-environment -- IV. A glossary of tetrads. Tedradic glossary.
Includes index and bibliography: page [199]-205.
Keywords: Mass media -- Technological innovations; Mass media -- Social aspects; Technology -- Social aspects